2023
DOI: 10.1002/cbdv.202300346
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Pleurotus ostreatus Grown on Sisal Agro‐Industrial Waste Supplemented with Cocoa Almond Tegument and Wheat Bran

Caline G. Ferraz,
Paulo R. Ribeiro,
Brenno V. Verde
et al.

Abstract: Pleurotus ostreatus is an edible fungus with high nutritional value that uses industrial and agricultural lignocellulosic residues as substrates for growth and reproduction. Understanding their growth metabolic dynamics on agro‐industrial wastes would help to develop economically viable and eco‐friendly biotechnological strategies for food production. Thus, we used UHPLC/MS/MS and GNPS as an innovative approach to investigate the chemical composition of two strains of P. ostreatus, coded as BH (Black Hirataki)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…It is observed that the nutrient content in Pleurotus ostreatus is similar to other research with 19.08%, 1.60%, 51.80%, and 5.49% in terms of protein, fat, carbohydrates, and ash, respectively [28]. Pleurotus ostreatus is an edible mushroom of high nutritional value that uses industrial and agricultural lignocellulosic waste as substrates for its growth and reproduction [29]. Changes in nutrient content and mineral composition are influenced by various factors and conditions such as substrate and growing supplements.…”
Section: Nutritional Composition Of Pleurotussupporting
confidence: 81%
“…It is observed that the nutrient content in Pleurotus ostreatus is similar to other research with 19.08%, 1.60%, 51.80%, and 5.49% in terms of protein, fat, carbohydrates, and ash, respectively [28]. Pleurotus ostreatus is an edible mushroom of high nutritional value that uses industrial and agricultural lignocellulosic waste as substrates for its growth and reproduction [29]. Changes in nutrient content and mineral composition are influenced by various factors and conditions such as substrate and growing supplements.…”
Section: Nutritional Composition Of Pleurotussupporting
confidence: 81%